Penerapan Senam Hamil Pada Ny. A Trimester 3 Dengan Nyeri Akut - Putri, Tias Sinta; Wijayanti, Kartika; Rohmayanti, Rohmayanti (Borobudur Nursing Review, 2024)
Introduction: Pregnancy is something that is valuable and longed for by many women, but pregnancy causes changes both physically and psychologically. Back pain is a natural symptom and is often felt in the 3rd trimester of pregnancy, pain that causes discomfort can be overcome in non-pharmacological ways, namely by implementing pregnancy exercise. Objektive: This study aims to apply pregnancy exercise to third trimester pregnant women with acute pain. Method: The method used in this research is a case study, with a sampling method that is purposive sampling. The sample taken in this study was a pregnant woman with moderate back pain score 5, the data was taken using participatory observation methods, unstructured interviews and documentation. After collecting existing data analyzed using domain analysis. Result: The results showed that pregnancy exercise in respondents could reduce back pain that occurred in third trimester pregnant women from a score of 5 to 2 within 8 days of intervention. Conclusion: Pregnancy exercise can reduce pain in third trimester pregnant women.